Computers, laptops and tools - Ainley, Mary.; Bourke, Valerie; Chatfield, Robert; . (Camberwell, Vic. : Australian Council for Educational Research, 2000)
Introduction. In their own words. The diary entries. Emotions, motivation and engagement. Tools in the box and on the shelf. Staff and parents have a say.
Keywords: Education; Data processing; Education -- Victoria -- Data processing; Laptop computers -- Victoria; Computer-assisted instruction -- Victoria